Identification of Forest City Multi-Policy Using the MULTIPOL: A Study In The New Indonesian Capital, East Kalimantan - Wijaya, Hengky; Kusmana, Cecep; Rusdiana, Omo; Rushayati, Siti Badriyah (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2024)
The policy-planned development in the new Indonesia Capital City (IKN) area must be accompanied by good planning to ensure the continued availability of forestry ecosystem services, especially forestry areas. These ecosystem services are strongly influenced by their ecological functions. Humans depend on essential ecosystem services to satisfy their inherent needs and enhance or preserve their quality of life. Natural resources are being overused to satisfy these demands, endangering biodiversity and putting more strain on ecosystems. Therefore, a multi-policy approach describes and visualizes the relationships between multi-aspect policies that provide and benefit from forestry ecosystem services. The method used in compiling this paper is multi-policy, part of the prospective analysis method. This method will map and create a model, the best policy scenario that can be applied to achieve the goal of a forest city in the new nation's capital. The results show that the presidential regulation implementation scenario is the best policy choice for the forest city model in the new state capital.